The Role of International Intervention in Supporting and Sustaining Internal Armed Conflict and Its Impact on Political and Economic Stability in Sudan - Thahab Mahou, Lect. Heba (Basra studies journal, 2025)
This study examines the issue of international intervention in internal armed conflicts in Sudan, aiming to analyze the role such interventions play in shaping the country’s political and economic stability. The research is grounded in a central question regarding the effectiveness of international intervention in resolving conflicts and achieving peace, and whether such intervention contributes to ending the crisis or further complicates it. The study focuses on the complex interplay between the legal and political considerations that govern international intervention, as well as its direct and indirect impacts on Sudan’s internal conditions